The method of correction of the training process in the powerlifting using the facilities of the speed-power education on the stage of the previous basic training - Ніжніченко [Dmitro Nizhnichenko], Дмитро Олександрович (Slobozhanskyi Herald of Science and Sport, 2013)
The method of correction of the training process is developed in powerlifting using the facilities of speed-power education on the stage of the previous basic training. The author’s method includes exercises with using different treatments of muscles’ operations: static and dynamic, isokinetic, pliometric. The depth jumps and jumping exercises were at the special place in this program. Introduction of the author’s method to the educational-training process in powerlifting provided the overwhelming increase of the special physical qualities in an experimental group against the indexes of control one. The results of the conducted factor analysis testify that morphological indexes, power and speed-power preparedness play the leading role in the structure of the training process in powerlifting on the stage of the previous basic training.